Jurnalisme Indonesia di Era Disrupsi Informasi - Eko Sumardi; Indah Suryawati (PROPAGANDA, 2022)
The phenomenon of online journalism requires that some providers of news content in conventional media transform themselves into multiplatform. It aims to be able to survive in the competition of the media industry. Not surprisingly, most of the conventional news media that still survive today have sites on the internet. Some only follow content from the parent company, but some others only provide additional material. These related sites operate to the same standards of practice and professionalism as their parent company does. It could be said that journalism is entering a time called a period of disruption. A period of disruption is a time when change occurs so unexpectedly, is fundamental and touches almost all joints of people's lives. And the presence of online journalism has revolutionized news where speed is a major factor. News is no longer an 'already ongoing' event, but an 'ongoing' event that should be broadcast by the media. Some features in online journalism are actually cited as a variety of causes of the erosion of idealism and credibility in online journalism. The impact of internet technology caused the online news media to undergo a radical revolution that made it different from journalism in the mass media in general.